The Financial Accountability of e-Government: The Information Transparency of Decision-making Processes in Public Organizations - GHERASIM, Zenovic; IONESCU, Luminita (Annals of Spiru Haret University. Economic Series, 2019)
Effective e-Government can contribute to the modernization of the public sector administration, and increase the efficiency in the activity of governments and national agencies facilitating the participation of citizens in the social and political life. The use of e-Government improves the electronic transactions between government agencies, companies and citizens, in order to improve the quality of the services and to increase the transparency in the public financial sector. The recent reforms in the public financial management are accelerated by new technologies and are creating the premises for a disciplined, transpired and flexible public sector administration. After a presentation of recent views from literature on some main problems of e-government and software services, the research is focused on the development of e-government and public finance administration.